2008
DOI: 10.1016/j.bmc.2008.01.044
|View full text |Cite
|
Sign up to set email alerts
|

Constrained NBMPR analogue synthesis, pharmacophore mapping and 3D-QSAR modeling of equilibrative nucleoside transporter 1 (ENT1) inhibitory activity

Abstract: Conformationally constrained analogue synthesis was undertaken to aid in pharmacophore mapping and 3D QSAR analysis of nitrobenzylmercaptopurine riboside (NBMPR) congeners as equilibriative nucleoside transporter 1 (ENT1) inhibitors. In our previous study (Zhu et al., J. Med. Chem. 46, 831-837, 2003), novel regioisomeric nitro-1, 2, 3, 4-tetrahydroisoquinoline conformationally constrained analogues of NBMPR were synthesized and evaluated as ENT1 ligands. 7-NO 2 -1, 2, 3, 4-tetrahydroisoquino-2-yl purine ribosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…5B) as ENT1 inhibitors. The most suitable substitution position of the nitro group was explored by varying its position on the aromatic ring of the tetrahydroisoquinone moiety [332,333]. In addition, novel fluorescent substrates have also been produced for probing transporter activity [334].…”
Section: Recently Developed Drugs Acting On the Adenosinergic System mentioning
confidence: 99%
“…5B) as ENT1 inhibitors. The most suitable substitution position of the nitro group was explored by varying its position on the aromatic ring of the tetrahydroisoquinone moiety [332,333]. In addition, novel fluorescent substrates have also been produced for probing transporter activity [334].…”
Section: Recently Developed Drugs Acting On the Adenosinergic System mentioning
confidence: 99%
“…hCNT2 seemed to involve primarily H-bond interactions while hCNT1 utilized electrostatic and steric interactions as well. 63 Two studies 64,65 described 3D QSAR results of NBMPR analogues and their interaction with hENT1 which not only agreed with prior research, but correlated with an NMR study 66 which demonstrated an anti-configuration rather than the syn configuration seen in X-ray diffraction and X-ray crystals of NBMPR. 67,68 Ho et al did a study on hENT4 in which they looked at substrate and inhibitor structure-activity relationships at physiological pH.…”
Section: Chapter 2 Computer Modeling Studies Introductionsupporting
confidence: 66%
“…Considering NBMPR possesses a nitro group, and dipyridamole and its potent analogues lack such a highly polar and strong hydrogen bond acceptor group, this prediction correlates with the chemical functionality. As the position of the nitro substituent greatly effected potency, 64 this suggested that steric interaction played a more important role in NBMPR analogue potency compared to the dipyridamole analogues, suggesting that this portion of the molecules may occupy the non-overlapping regions of the binding sites for hENT1.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we used a highly selective inhibitor of ENT1, NBMPR, to demonstrate that ENT1 inhibition is sufficient to block the effect of AICAR on HGP and AMPK signalling. Molecular docking data are unavailable for 8CPT‐cAMP analogues docking to ENT1 but in contrast, robust 3D‐Quantitative Structure‐Activity Relationship analysis is available for NBMPR/ENT1 interaction 30, 31, 32. NBMPR did not alter the effects of metformin on AMPK and HGP.…”
Section: Discussionmentioning
confidence: 97%